Teacher's guide to tackling attendance challenges - Sprick, Jessica; Berg, Tricia (ASCD, 2019)
"This book focuses on creating a classroom culture of attendance. Advocating moving away from traditional approaches used to address the problem of absenteeism, which do too little too late and focus on trying to punish away absenteeism problems, the book will help teachers reduce the magnitude of attendance problems through universal prevention"--